Representing Cyberbullying Perpetrators in Indonesian Digital Media: A Critical Discourse Analysis of the Jakarta Post - Erika Agustiana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines how cyberbullying perpetrators are portrayed in Indonesian digital media through a Critical Discourse Analysis (CDA) of "Online Evil: Indonesia's Cyberbullying Problem" published by The Jakarta Post. It explores the linguistic representation of cyberbullying perpetrators and how such portrayals reflect social ideologies and digital culture in Indonesian society. Using a qualitative approach, the study applies Norman Fairclough's three-dimensional CDA framework alongside social actor representation theory and transitivity analysis. Data consisting of words, phrases, clauses, and sentences were collected through documentation and close reading, then analysed at micro, meso, and macro levels. Findings reveal that perpetrators are depicted through negative word choices, aggressive metaphors, transitivity patterns, and collectivization strategies. Anonymous perpetrators are framed as aggressive and destructive figures through expressions like "internet trolls" and "hateful comments", while relational perpetrators are represented collectively through social actor categorization. The study also shows that cyberbullying discourse is closely tied to digital pragmatics, including face-threatening acts, impoliteness, and online identity negotiation. Media narratives construct cyberbullying as symbolic violence and a social threat in digital spaces. These findings suggest that media discourse not only reports cyberbullying but also reproduces ideologies about deviant digital behaviour. Pedagogically, this study contributes to digital pragmatics and critical digital literacy instruction within Outcome-Based Education (OBE) frameworks in higher education.